Information publicity and resident’s waste separation behavior: An empirical study based on the norm activation model - Wang, Shanyong; Wang, Jinpeng; Zhao, Shuliang; Yang, Shu (Waste management (Elmsford), 2019)
•This study explores how information publicity affects waste separation intention.•A questionnaire survey is conducted to collect the research data.•Information publicity has a limited direct effect on waste separation intention.•Personal norm has the largest effect on waste separation intention.•Information quality positively moderates the effect of information publicity. Waste separation is beneficial to minimize the negative environmental effects of waste and to promote the recycling use of waste. Based on the norm activation model framework, this study mainly focused on examining how information publicity about waste separation affects resident’s waste separation intention. A questionnaire survey was conducted in China to collect the research data, and the data were analyzed by using the structural equation modeling technique. The results indicated that resident’s awareness of consequences of not separating waste is positively and significantly associated with ascription of responsibility, and both of them are positively and significantly related to personal norm. Personal norm is positively associated with resident’s waste separation intention. Furthermore, information publicity has a direct and positive effect on resident’s waste separation intention. However, the effect is relatively small. Meanwhile, it is worth noting that the effect of information publicity on waste separation intention depends on information quality. Information quality positively moderates the effect of information publicity on waste separation intention. The current study enriched the research on resident’s waste separation behavior and highlighted the role of information publicity. Based on the results, policy implications about how to motivate residents to separate waste were discussed and the research limitations were pointed out.